Concentration for self-bounding functions and an inequality of Talagrand. - McDiarmid, C; Reed, B (2006)
We see that the entropy method yields strong concentration results for general selfbounding functions of independent random variables. These give an improvement of a concentration result of Talagrand much used in discrete mathematics. © 2006 Wiley Periodicals, Inc.